Assessment of characteristic failure envelopes for intact rock using results from triaxial tests - Muralha, J. (2015)
The paper presents contributions to the statistical study of the parameters of the Mohr-Coulomb and Hoek-Brown strength criteria, in order to assess the characteristic failure envelopes for intact rock, based on the results of several sets of triaxial tests performed by LNEC.